Literature Study of Specific Phobias (Nomophobia) from an Islamic Perspective - Hastuti, Novita Puji (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: Phobia is an anxiety disorder with symptoms of feeling afraid excessively of something usually not dangerous . Phobias can be experienced by anyone without looking at type gender, age, and social status economy . The purpose of this study is to describe one type of a specific phobia called Nomophobia from an Islamic perspective. The term NOMOPHOBIA or NOMObilePhonePhoBIA is used to describe a psychological condition in which the individual fears excessively regardless of cell phone connectivity. The term NOMOPHOBIA builds on the definition described in the DSM-IV, it has been labeled as "the phobia of specific things". Methodology: The writing of this research uses the method of library research or library research. In this study, both books, journals, articles and facts related to nomophobia were collected Results : The results of this study will provide an explanation of what nomophobia is, its causes, factors and how to overcome it according to an Islamic perspective. The main factors of nomophobia are internal factors, external factors and the demands of the times. Cognitive Behavioral Therapy and Islamic counseling are ways to overcome nomophobia.